Imputação objetiva e conduta da vítima - Johner, Marcos Afonso (2021)
This dissertation verifies how the victim's conduct can influence the criminal responsibility of the author, within the scope of imputation to the objective type. In order to achieve the proposed objective, using the hypothetical-deductive approach method, is held an incursion into the various issues involving imputation in the event of lesions to individual legal assets, mainly life, physical integrity and health. At first, the fundament and the categories of imputation to the objective type are approached, defining its structure and the respective criteria. Following, the research exposes some aspects of victimology and victimodogmatic, as well as categories that offer answers to cases of victim intervention in the harmful course. Space in which if you're looking for also to demonstrate why the victim's conduct should be into account, from the aspects of autonomy and self-responsibility. Finally, the work proposes to concretize the foundations hitherto demarcated, in order to define the imputation criteria in cases where the victim's conduct contributes to the occurrence of the fact. The dissertation focuses on the area of Criminal System and Violence, and the Contemporary Legal-Criminal Systems Research Line.